Multiple stab wounds on the left side of the chest in a patient with Situs Inversus Totalis: A lifesaving coincidence. (2020) - Escobar Capriata, Ismael; Ternes, Caique Martins Pereira; Ternes Rech, João Vítor; Kuhn Mesacasa, Franciele; Amaral, Robson; Franzon, Orli
Highlights: Sinus Inversus totalis is a rare condition and the diagnosis may be incidental. Reports of surgery in patients with Situs Inversus Totalis are very rare, especially in trauma. Outcomes of emergency surgeries in patientes with Sinus Inversus Totalis can be different than those expected in the general population due to anatomical differences. Abstract: Introduction: Situs Inversus Totalis (SIT) is a rare finding of complete reversal of the thoracic and abdominal organs with an estimated incidence of 0.005%–0.01% in the population. Severe trauma has not been reported in this population. We present a case of multiple chest stab wounds in a patient with previously unknown SIT. Presentation of case: A 39-year-old male was admitted to the emergency room with multiple stab wounds on the left side of the chest. Upon admission the patient was hypotensive, with miosis and intubated. Significant ECG findings were an inverted P wave, inverted QRS complex and inverted T wave in V1. A chest CT scan showed SIT, hemopneumothorax on the left side and, despite multiple stab wounds on the left side of the chest, no cardiac damage. The surgical team decided for a conservative approach and the patient remained in the ICU for two days. After five days he was discharged in good clinical conditions. Discussion: SIT generally does not have a clinical relevance throughout the patients life and most diagnoses are coincidental. However, when discovered in acute surgical cases, it requires an accurate evaluation by the surgical team due to anatomical differences that may produce undesirable outcomes in emergency cases such as appendicitis and general trauma. Conclusion: There have been very few reports of SIT and trauma in the medical literature. This might be the first ever reported case of a patient with SIT who suffered multiple stab wounds on the left side of the chest and was saved because of his condition.